Anticholinergic medicines in an older primary care population: a cross‐sectional analysis of medicines' levels of anticholinergic activity and clinical indications. (27th June 2016) - Magin, P. J.; Morgan, S.; Tapley, A.; McCowan, C.; Parkinson, L.; Henderson, K. M.; Muth, C.; Hammer, M. S.; Pond, D.; Mate, K. E.; Spike, N. A.; McArthur, L. A.; et al.
Summary: What is known and objectives: Adverse clinical outcomes have been associated with cumulative anticholinergic burden (to which low‐potency as well as high‐potency anticholinergic medicines contribute). The clinical indications for which anticholinergic medicines are prescribed (and thus the 'phenotype' of patients with anticholinergic burden) have not been established. We sought to establish the overall prevalence of prescribing of anticholinergic medicines, the prevalence of prescribing of low‐, medium‐ and high‐potency anticholinergic medicines, and the clinical indications for which the medicines were prescribed in an older primary care population. Methods: This was a cross‐sectional analysis of a cohort study of Australian early‐career general practitioners' (GPs') clinical consultations – the Registrar Clinical Encounters in Training (ReCEnT) study. In ReCEnT, GPs collect detailed data (including medicines prescribed and their clinical indication) for 60 consecutive patients, on up to three occasions 6 months apart. Anticholinergic medicines were categorized as levels 1 (low‐potency) to 3 (high‐potency) using the Anticholinergic Drug Scale (ADS). Results: During 2010–2014, 879 early‐career GPs (across five of Australia's six states) conducted 20 555 consultations with patients aged 65 years or older, representing 35 506 problems/diagnoses. Anticholinergic medicines were prescribed in 10·4% [95% CIs 9·5–10·5] of consultations. Of the total anticholinergic load of prescribed medicines ('community anticholinergic load') 72·7% [95% CIs 71·0–74·3] was contributed by Level 1 medicines, 0·8% [95% CIs 0·5–1·3] by Level 2 medicines and 26·5% [95% CIs 24·8–28·1] by Level 3 medicines. Cardiac (40·0%), Musculoskeletal (16·9%) and Respiratory (10·6%) were the most common indications associated with Level 1 anticholinergic prescription. For Level 2 and 3 medicines (combined data), Psychological (16·1%), Neurological (16·1%), Musculoskeletal (15·7%) and Urological (11·1%) indications were most common. What is new and conclusion: Anticholinergic medicines are frequently prescribed in Australian general practice, and the majority of the 'community' anticholinergic burden is contributed by 'low'‐anticholinergic potency medicines whose anticholinergic effects may be largely 'invisible' to prescribing GPs. Furthermore, the clinical 'phenotype' of the patient with high anticholinergic burden may be very different to common stereotypes (patients with urological, psychological or neurological problems), potentially making recognition of risk of anticholinergic adverse effects additionally problematic for GPs. Abstract : Level 1, Level 2 and 3 combined, and total anticholinergic medicines, by ICPC‐2 chapter.